2015–2016 Vaccine Effectiveness of Live Attenuated and Inactivated Influenza Vaccines in Children in the United States. (4th October 2017) - Poehling, Katherine A; Caspard, Herve; Peters, Timothy R; Belongia, Edward A; Congeni, Blaise; Gaglani, Manjusha; Griffin, Marie R; Irving, Stephanie A; Kavathekar, Poornima K; McLean, Huong Q; Naleway, Allison L; Ryan, Kathleen; et al.
Abstract : This test-negative case-control study showed live attenuated influenza vaccine and inactivated influenza vaccine were effective against any influenza in 2015–2016. Abstract: Background: In the 2015–2016 season, quadrivalent live attenuated influenza vaccine (LAIV) and both trivalent and quadrivalent inactivated influenza vaccine (IIV) were available in the United States. Methods: This study, conducted according to a test-negative case-control design, enrolled children aged 2–17 years presenting to outpatient settings with fever and respiratory symptoms for <5 days at 8 sites across the United States between 30 November 2015 and 15 April 2016. A nasal swab was obtained for reverse-transcriptase polymerase chain reaction (RT-PCR) testing for influenza, and influenza vaccination was verified in the medical record or vaccine registry. Influenza vaccine effectiveness (VE) was estimated using a logistic regression model. Results: Of 1012 children retained for analysis, most children (59%) were unvaccinated, 10% received LAIV, and 31% received IIV. Influenza A (predominantly antigenically similar to the A/California/7/2009 strain) was detected in 14% and influenza B (predominantly a B/Victoria lineage) in 10%. For all influenza, VE was 46% (95% confidence interval [CI], 7%–69%) for LAIV and 65% (48%–76%) for IIV. VE against influenza A(H1N1)pdm09 was 50% (95% CI, −2% to 75%) for LAIV and 71% (51%–82%) for IIV. The odds ratio for vaccine failure with RT-PCR–confirmed A(H1N1)pdm09 was 1.71 (95% CI, 0.78–3.73) in LAIV versus IIV recipients. Conclusions: LAIV and IIV demonstrated effectiveness against any influenza among children aged 2–17 years in 2015–2016. When compared to all unvaccinated children, VE against influenza A(H1N1)pdm09 was significant for IIV but not LAIV. Clinical Trials Registration: NCT01997450